Russian-Speaking Immigrants in Post-Soviet Estonia: Towards Generation Fragmentation or Integration in Estonian Society. (May 2017) - Saar, Ellu; Krusell, Siim; Helemae, Jelena
The disadvantages experienced by immigrants in education and labour markets have been of growing concern in many countries in recent years. However, little research has been undertaken on ethnic inequalities in labour markets in Eastern Europe, and especially in post-Soviet societies. This article considers the integration of the immigrant population into the labour market in post-Soviet Estonia, where the context and peculiarities of the arrived population are quite different from the assumptions of Western immigrant integration theories. The Russian-speaking population arrived in Estonia after World War II as internal migrants, because Estonia was part of the Soviet Union. A remarkably high proportion of them were well educated. After Estonia regained its independence in 1991, the context of integration changed radically, and the legal status of internal Soviet Union migrants was redefined. To account for these societal and political changes, we suggest making an analytical distinction between generations of immigrants in a demographic sense (being born in Estonia) and an integrational sense (becoming an integral part of the host society, in the labour market - having more similar patterns to those of the native population in the context of labour market outcomes). This distinction impacts differently on different age cohorts and we analysed outcomes of labour market integration alongside both nativity generations and age cohorts. Our analysis based on the 2011-2013 Labour Force Surveys shows that, while in most Western countries there are tendencies of convergence between natives and second-generation immigrants regarding structural integration, in Estonia the dynamics are different. The net disadvantage of young second-generation immigrants relative to their Estonian counterparts is either more pronounced compared to the disadvantage of their 'parents' age cohort relative to their Estonian peers (with regard to the risks of unemployment or chances of obtaining a high occupational position) or becoming less pronounced, but only for the highly educated portion of second generations (in terms of self-assessed over-education).